Densification mechanism of deep low-permeability sandstone reservoir in deltaic depositional setting and its implications for resource development: A case study of the Paleogene reservoirs in Gaoshangpu area of Nanpu sag, China - Wang, Shilin; Yang, Xiran; Lu, Yuanyuan; Su, Peidong; Liu, Dong; Meng, Lingjian; Wang, Qi; Li, Liang; Radwan, Ahmed E. (Frontiers in Earth Science, 2022)
A better understanding of reservoir densification mechanisms is very important for petroleum exploration and controlling the reservoir quality distribution in low-permeability reservoirs. Low porosity and low permeability, difficult reconstruction, and economic infeasibility are important factors restricting its efficient production. Systematic analysis was performed to study the evolution of different microfacies in the deltaic depositional setting of the Paleogene deep low-permeability Gaoshangpu reservoir, define their genetic mechanisms, delineate the dominant facies belts, and define the favorable diagenetic sequences that are important for exploration of high-quality reservoirs. To understand the tight genesis of the low-permeability reservoirs, we analyzed the sedimentological and diagenetic evolution characteristics of various microfacies (i.e., underwater distributary channel, distributary bay, mouth bar, and front sheet sand) using core data and physical property analysis of the reservoir sand body. The results show the underwater distributary channel and estuary bar sand body with medium-to fine-grained and poor–medium sorting. The diagenesis is dominated by strong compaction, calcareous, argillaceous cementation, and dissolution during stage B in early diagenesis and stage A in middle diagenesis. In the fan delta environment, the weak anti-compaction resistance of low-permeability reservoirs is mainly due to the large content of plastic particles, finer grain size, and medium–poor sorting, with an average porosity reduction rate of 65%. This is a key factor for densification of reservoirs above 3000 m. Comparison among different sandstone microfacies of the deltaic setting shows that the sand body of the underwater distributary channel with low shale content has slightly stronger compaction resistance. The porosity reduction is not obvious at the depth of 3,000–4,000 m, but the loss of permeability at this depth section is significant, and the reservoir improvement from later dissolution is most obvious at this depth section. Calcareous cementation is the cause for densification of some mouth bars in the early stage and of underwater distributary channels in the middle and late stage. Under the influence of strong compaction and calcareous-filling pore throat, the sand body of the mouth bar has been basically densified at 3,000 m, resulting in limited reservoir transformation from later dissolution. The study shows that compaction is the main cause of reservoir densification, argillaceous and calcareous cementation is the secondary cause, and later dissolution is another main cause of reservoir enhancement. The research results can provide a reference and direction for reservoir development and search for the high-quality sweet spot in the deep and low-permeability reservoir.